On a case of hydatid cyst of the concave surface of the liver with early jaundice - Odriozola, Ernesto (1918)
The case is now going to deal, is one of those who seem vulgar for its ostensible appearance, but really strange, because it is a rarity among us; at least it is the first time we have the opportunity to observe and said by the way, are still not very numerous specimens of this species in the scientific literature.